Multistep short-term wind speed prediction using nonlinear auto-regressive neural network with exogenous variable selection - Noman F.; Alkawsi G.; Alkahtani A.A.; Al-Shetwi A.Q.; Kiong Tiong S.; Alalwan N.; Ekanayake J.; Alzahrani A.I. (Elsevier B.V., 2023)
Electric power transmission networks; Forecasting; Mean square error; Neural networks; Predictive analytics; Speed; Transfer learning; Wind; Wind power; Exogenous variables; Multi-step prediction; Neural networks (NNS); Root mean square errors; Short-term wind speed predictions; Transfer learning methods; Variable selection methods; Wind speed prediction; Learning systems